The Application of AI Technology in Industrial Management - Chen, Meixin (Journal of Theory and Practice of Management Science, 2025)
Artificial intelligence (AI) has profoundly impacted various industries, and its application in industrial management has become increasingly significant. This paper explores the multifaceted applications of AI in industrial management, emphasizing its role in enhancing efficiency, optimizing operations, improving product quality, and predicting equipment failures. By leveraging recent research and practical examples, we demonstrate how AI can revolutionize traditional manufacturing processes and bolster competitiveness in the global market. Furthermore, we discuss the ethical implications and future directions of AI in industrial management.